Resistance and virulence gene analysis and molecular typing of Escherichia coli from duck farms in Zhanjiang, China - Luo, Shuaishuai; Liao, Cuiyi; Peng, Jinju; Tao, Songruo; Zhang, Tengyue; Dai, Yue; Ding, Yuexia; Ma, Yi (Frontiers in Cellular and Infection Microbiology, 2023)
The widespread use of antibiotics in animal farms has increased the resistance of Escherichia coli (E. coli), pathogenic E. coli often carries complex virulence factors. Antimicrobial resistance in pathogenic bacteria causes public health problems through the food chain. Therefore, the correlation analysis of resistance, virulence and serotype of pathogenic bacteria in farms and surrounding environment is great significance to public health. To explore the drug resistance genes and virulence genes and molecular typing characteristics of E. coli from duck farms in Zhanjiang area. In this study, 30 strains of E. coli were isolated from duck farms in Zhanjiang area. PCR method was used to detect drug resistance gene, and the virulence gene, serotype and multilocus sequence typing were analyzed by whole-genome sequencing. The detection rate of oqxA resistance gene was the highest (93.3%). fimC virulence gene detection rate was the highest(93.3%).There was no correlation between drug resistance gene number and virulence gene number in the same strain.The epidemic serotype was O81(5/24), ST3856 was an epidemic ST type, Ⅰ-9 and Ⅲ-6 strains carried 11 virulence genes.The E. coli strains from duck farms in Zhanjiang area had abundant drug resistance spectrum, various virulence genes, complex serotypes, and certain pathogenicity and genetic relationship.Therefore, it is necessary to strengthen rational monitoring and guidance of the spread of pathogenic bacteria and the use of antibiotics in the livestock and poultry industry of Zhanjiang area.